The role of trust in mediating the influence of influencer marketing and online customer reviews on hmns perfume purchase decisions - Putri, Ayu Putu Diah Pradnyani; Kustina, Ketut Tanti (EDUCTUM: Journal Research, 2026)
The development of digital marketing has led to the increasing use of influencer marketing and online customer reviews as strategies to influence consumer purchasing decisions, particularly for sensory experience-based products such as perfume. This study aims to analyze the influence of influencer marketing and online customer reviews on purchasing decisions, with trust as a mediating variable among HMNS perfume consumers on the Shopee platform. The research approach used a quantitative method by distributing questionnaires to 140 Gen Y and Gen Z consumer respondents in Bali who had purchased HMNS perfume through Shopee. The data analysis technique used Partial Least Square (PLS). The results showed that influencer marketing and online customer reviews had a positive and significant effect on trust. In addition, trust had a positive and significant effect on purchasing decisions. These findings also indicate that trust can significantly mediate the influence of influencer marketing and online customer reviews on purchasing decisions. These results confirm that increasing consumer trust is key to strengthening the effectiveness of digital marketing strategies in driving perfume product purchasing decisions. The practical implications of this study emphasize the importance of selecting credible influencers and managing customer reviews to build consumer trust and increase sales.